2013
DOI: 10.1016/j.beproc.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the past and planning for the future in rats

Abstract: A growing body of research suggests that rats represent and remember specific earlier events from the past. An important criterion for validating a rodent model of episodic memory is to establish that the content of the representation is about a specific event in the past rather than vague information about remoteness. Recent evidence suggests that rats may also represent events that are anticipated to occur in the future. An important capacity afforded by a representation of the future is the ability to plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 87 publications
(136 reference statements)
2
39
0
Order By: Relevance
“…Rats apparently remember the source by which information was acquired, in addition to other features of the episode (location, flavour and retrieval cue). Elsewhere we showed that source memory is hippocampal dependent [6] and that retrieval of episodic information can occur when encoding is incidental and memory assessment is unexpected [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Rats apparently remember the source by which information was acquired, in addition to other features of the episode (location, flavour and retrieval cue). Elsewhere we showed that source memory is hippocampal dependent [6] and that retrieval of episodic information can occur when encoding is incidental and memory assessment is unexpected [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Zentall and colleagues have argued that when information is encoded for use in an expected memory test, explicitly encoded information may generate a planned action; thus, at the time of the test, the remembered action can occur successfully without remembering any earlier episodes. The central hypothesis of an animal model of episodic memory is that, at the moment of memory assessment, the animal remembers back in time to the event or episode (Crystal, 2013b(Crystal, , 2016a(Crystal, , 2016b; the focus on retrieving a memory of the earlier event is the key element that makes an animal model of episodic memory episodic. Therefore, carrying forward information that is needed at a future test while not specifically retrieving a memory of the earlier episode represents a serious threat to the episodicmemory hypothesis.…”
Section: Incidental Encoding and Unexpected Questionsmentioning
confidence: 99%
“…Therefore, carrying forward information that is needed at a future test while not specifically retrieving a memory of the earlier episode represents a serious threat to the episodicmemory hypothesis. Thus, it is necessary to rule out the hypothesis that accurate performance in the test is based on a planned action generated when information was explicitly encoded rather than a memory of the episode (Crystal, 2013b;Singer & Zentall, 2007;Zentall et al, 2001;Zentall et al, 2008;Zhou & Crystal, 2011). Notably, it is possible that animals may have solved previous tests of episodic memory by using learned semantic rules without remembering the episode.…”
Section: Incidental Encoding and Unexpected Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most used tasks are the object recognition task, and variations thereof (Dere et al 2006;Ennaceur and Delacour 1988;Kesner et al 2008). Other examples are specific procedures in radial mazes (Crystal 2013), odor recognition (Eichenbaum et al 2010), and some procedures in the classic Morris water task (Zhang et al 2008). For all these test mentioned, the "what," "where," and "when" can be applied.…”
Section: How To Measure Declarative Episodic Memory In Animalsmentioning
confidence: 98%